Inside Cover: A Stable Porous Anionic Metal–Organic Framework for Luminescence Sensing of Ln3+ Ions and Detection of Nitrobenzene (Chem. Asian J. 3/2014). Issue 3 (March 2014) - Qin, Jun‐Sheng; Bao, Shao‐Juan; Li, Peng; Xie, Wei; Du, Dong‐Ying; Zhao, Liang; Lan, Ya‐Qian; Su, Zhong‐Min
<x xml:space="preserve">Abstract</x> Metal–Organic Frameworks (MOFs) Dual functional materials with high chemical stability that not only act as a fluorescent probe for different lanthanide (Ln3+) ions but can also be used for detection purposes are difficult to obtain. In their Communication on page 749 ff. (highlighted on the Inside Cover), Ya‐Qian Lan, Zhong‐Min Su et al. report on a microporous anionic MOF with a honeycomb shape that serves as a host for the encapsulation of Ln3+ ions. The MOF exhibits luminescent sensing with preference towards Eu3+ and Tb3+ ions over Sm3+ and Dy3+ ions. Moreover, it represents a potential recyclable luminescent probe for the sensitive detection of nitrobenzene through fluorescence quenching.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>